Wind generator and storage system scheduling for customer benefit and battery life - Neelakantha Guru; Samarjit Patnaik; Manas Ranjan Nayak; Meera Viswavandya (Bulletin of Electrical Engineering and Informatics, 2023)
Due to increased fossil fuel use and fossil fuel limitations, the Indian energy industry is migrating to non-conventional energy resources such as solar power, wind production, and fuel cells, among others. The unpredictability of non-conventional energy sources makes it difficult to balance an electrical system when they are incorporated, necessitating the incorporation of a storage device into the grid. In a microgrid system with wind turbine generation (WTG) and a battery energy storage system (BESS), the BESS may reserve energy during periods of surplus generation and release it to the grid during times of peak demand. The suggested technique establishes the state of charge (SOC) schedule for the BESS by employing an artificial rabbit optimisation (ARO) algorithm that minimises energy costs for customers. The state of health (SOH) of the energy storage is incorporated as an ageing coefficient, which causes the BESS to behave conservatively in order to retain its lifespan. Using a time of use (TOU) tariff, simulation results suggest a substantial possibility to boost the savings of consumers in a grid-connected micro-grid. The simulation findings indicate that by efficiently scheduling the BESS power management technique, the proposed method improves a number of distribution system efficacy.